The diagnostic value of IgG index versus oligoclonal bands in cerebrospinal fluid of patients with multiple sclerosis - Simonsen, Cecilia Smith; Flemmen, Heidi Øyen; Lauritzen, Trine; Berg-Hansen, Pål; Moen, Stine Marit; Celius, Elisabeth Gulowsen (Multiple sclerosis journal - experimental, translational and clinical, 2020)
Background Diagnostic criteria for multiple sclerosis have been developed to guide the diagnostic process. In the latest revision of the McDonald criteria, the presence of oligoclonal bands may replace the need for dissemination in time. The aim of this study is to investigate if the less time-consuming analysis of immunoglobulin G index in cerebrospinal fluid can safely predict the findings of oligoclonal bands. Methods This is a retrospective study of patients with multiple sclerosis at three hospitals in South-East Norway where lumbar puncture is performed routinely. We included patients diagnosed with multiple sclerosis after 2005 with known oligoclonal band status and an immunoglobulin G index score. Results Of 1295 patients diagnosed during or after 2005, 93.8% were oligoclonal band positive at diagnosis. Of 842 multiple sclerosis patients with known immunoglobulin G index and oligoclonal band status, 93.3% were oligoclonal band positive and 76.7% had an elevated immunoglobulin G index. The positive predictive value of a high immunoglobulin G index when oligoclonal bands are positive was 99.4% (95% confidence interval 98.4–99.8%). The negative predictive value of a normal immunoglobulin G index when oligoclonal bands are negative was 26.5% (95% confidence interval 23.5–29.9%). Conclusion An immunoglobulin G index >0.7 has a positive predictive value >99% for oligoclonal bands. An elevated immunoglobulin G index adds diagnostic value versus oligoclonal bands and saves time in the diagnostic process.